2010
DOI: 10.1007/s00436-010-1885-z
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of parasitism tissue by treatment of mice chronically infected with Trypanosoma cruzi with lignano lactones

Abstract: The reduction of parasitism tissue upon treatment with two lignano lactones, namely (-)- cubebin (CUB) and (-)-hinokinin (HNK), was evaluated in the chronic phase of Chagas' disease by quantifying the enzyme beta-galactosidase expressed by the CL B5 clone strain of Trypanosoma cruzi. Tissue karyometry was also performed. Treatment with the assessed lignans led to a larger reduction in parasitism tissue in all evaluated organs, compared with benznidazole (BZN). Oral treatment with CUB or HNK was more effective.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…Among the several classes of plant-derived secondary metabolites, lignans constitute a class that displays a wide spectrum of biological activities (Apears et al, 2003), including their action against parasites that cause neglected tropical diseases such as trypanosomiasis (Saraiva et al, 2007;Esperandim et al, 2010) and leishmaniasis (Royo et al, 2003). In a previous work, our group found that (-)-cubebin from Piper cubeba (used in the semi-synthesis of DNK in the present work) did not kill Schistosoma mansoni but minimized the movement that occurred at concentrations of 100 and 200…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the several classes of plant-derived secondary metabolites, lignans constitute a class that displays a wide spectrum of biological activities (Apears et al, 2003), including their action against parasites that cause neglected tropical diseases such as trypanosomiasis (Saraiva et al, 2007;Esperandim et al, 2010) and leishmaniasis (Royo et al, 2003). In a previous work, our group found that (-)-cubebin from Piper cubeba (used in the semi-synthesis of DNK in the present work) did not kill Schistosoma mansoni but minimized the movement that occurred at concentrations of 100 and 200…”
Section: Discussionmentioning
confidence: 99%
“…Over the last few years, our team has evaluated the biological activity of extracts and compounds isolated from Piper cubeba against neglected parasitic diseases (Saraiva et al, 2007;Esperandim et al, 2010;Magalhães et al, 2012). The compound 3,4-bis ((6-nitrobenzo[d] [1,3]dioxol-5-yl)methyl)-dihydrofuran-2(3H)-one) ((-)-6,6´-dinitrohinokinin, DNK) is a dibenzylbutyrolactone lignan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The animals were infected with 100 trypomastigotes through intraperitoneal injection; inoculation conditions were selected based to the reported in previous studies in mice infected with T. cruzi in chronic phase [18, 19]. Mice were divided into five groups: negative control (CN): infected animals treated with PBS; positive control (CP): infected animals treated with allopurinol (8.5  μ g/g); hexane fraction (FHex): animals treated with the hexane fraction from the leaf crude extract of S. yucatanensis (41.6 mg·kg −1 ·day −1 ); dose 1 (D1): infected mice treated with a 20.8 mg·kg −1 ·day −1 1 : 4 mixture of lupenone and caryophyllene oxide; dose 2 (D2): infected mice treated with a 41.6 mg·kg −1 ·day −1 1 : 4 mixture of lupenone and caryophyllene oxide.…”
Section: Methodsmentioning
confidence: 99%
“…Previously discovered lignano lactones from the plant Piper cubeba [47] were shown to have in vivo activity in mice infected with T. cruzi (CL strain) [48]. Specifically, tissue parasites were reduced as low as 20% of control levels in mice given cubebin ( #8, Fig.…”
Section: Natural Productsmentioning
confidence: 99%